Indoor endotoxin and house dust mite concentrations in the canine homologue of human atopic dermatitis - Yunji Song; Yeji Kim; Jihyun Kim; Ha-Jung Kim (One Health)
Background: Household endotoxin exposure and house dust mite (HDM) allergens have been recently gaining attention for their immunological potential to affect allergic symptoms. Although dogs are spontaneous models of human atopic dermatitis (AD), there are few studies exploring their relationship. The aim of this study is to analyze the effects of HDM and endotoxin concentrations on AD in dogs and compare their immunological profiles with humans. Methods: We graded the canine AD Extent and Severity Index-4 (CADESI-4), Pruritus Visual Analogue Scale (PVAS), and transepidermal water loss (TEWL) in dogs with (n = 42) and without AD (controls; n = 18). Serum immunoglobulin E (IgE), interleukin (IL)-4, IL-31, and IL-33 levels were measured. Dog owners were required to answer residential environmental questionnaires and measure the average indoor relative humidity (RH) and temperature for 48 h. Dust samples were collected from the floor and analyzed for HDM allergens including Dermatophagoides farinae (Der f1) and D. pteronyssinus (Der p1) allergen and endotoxin. Results: Both the Der f1 concentration and endotoxin exposure levels from the floor dust had an inverse association with TEWL in dogs with AD (P < 0.05) but not in controls. Furthermore, the endotoxin concentration was negatively associated with the IL-4 level. No significant difference was found in endotoxin exposure and the Der f1 concentration between dogs with AD and controls. Conclusions: Indoor HDM exposure is associated with decreased TEWL, and endotoxin concentrations may contribute to the mitigation of CAD symptoms.